Stock PENGARUH RETURN ON ASSET (ROA), DEBT TO EQUITY RATIO (DER), DAN EARNING PER SHARE (EPS) TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2016-2018 - Ni Made Indah Purwitasari; Ni Putu Yuria Mendra; Desak Ayu Sriary Bhegawati (Jurnal Widya Akuntansi dan Keuangan, 2021)
Stock returns are the results obtained from investment activities. Returns can be divided into two, namely realized returns (returns that occur or can also be referred to as actual returns) and expected returns (expected returns by investors). To find out the return obtained, the investor can assess the company's performance sourced from the company's financial statements. This study aims to determine the effect of Return On Assets (ROA), Debt to Equity Ratio (DER), and Earning Per Share (EPS) on Stock Return. The sample in this study were 70 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Determination of the sample using a purposive sampling method, and obtained as many as 210. The analytical tool used is descriptive statistical analysis, the classic assumption test, multiple linear regression analysis and the model feasibility test. The results showed that the Return on Assets (ROA) and Earning Per Share (EPS) variables had a positive effect on stock returns. Even so, the Debt to Equity Ratio (DER) variable has no effect on stock returns.